Kommunale ressourcepersoners brug af de nationale tests - Kristoffer Brix Olesen (Cepra-Striben, 2018)
This article examines instructional coaches in the context of The Danish National Tests. Drawing on survey data collected from nine municipalities, which all have increased their focus on The Danish National Tests, the article examines the degree of knowledge the instructional coaches possess and the extent to which they use the test in their work. It is found, that instructional coaches, who works in the investigated municipalities, generally have knowledge about the tests. They do also overall use the test in several key areas as coaches for their co-teachers. Instructional coaches can have a positive influence on the use of data among their co-teachers, which can lead to changes in their practice and benefit pupil’s achievements.